Asymptotics of the Joint Distribution of Multivariate Extrema - Aksomaitis, A.; Jokimaitis, A. (Nonlinear Analysis: Modelling and Control, 2001)
Let Wn and Zn be a bivariate extrema of independent identically distributed bivariate random variables with a distribution function F. in this paper the nonuniform estimate of convergence rate of the joint distribution of the normalized and centralized minima and maxima is obtained.
Keywords: multivariate extreme value; limit distributions; convergence rate